Geronimo Stilton #41 : Mighty Mount Kilimanjaro - Bigolin, Silvia; Chiavini, Lorenzo; Ronchi, Roberto (Geronimo Stilton, 2010)
Bruce Hyena convinces Geronimo to join him in climbing Mount Kilimanjaro, a task for which the mouse journalist is completely unprepared.